Analisis Kemampuan Pemecahan Masalah dalam Menyelesaikan Soal HOTS Matematika Pokok Bahasan Peluang Siswa MAN Lhokseumawe - Fitri Rezeki; Lisa; Nur Anwar (Ar-Riyadhiyyat: Journal of Mathematics Education, 2021)
The purpose of this study was to describe mathematical problem solving abilities in solving Higher Order Thinking Skill (HOTS) questions on the subject of opportunities for permutations and combinations of MAN Lhokseumawe students. In general, students' mathematical problem-solving skills are still lacking in solving HOTS-shaped problems, both at the steps of understanding the problem, planning a solution, solving problems, and re-examining. This type of research uses a descriptive qualitative approach by providing problem-solving ability test questions in the form of HOTS and selecting interview subjects according to predetermined abilities. The results of the research on the percentage of students' answers to the steps of problem-solving skills are: understanding the problem 37%, planning a solution 51%, solving the problem 68%, and checking back 21%. So it can be concluded that students' mathematical problem solving abilities in solving HOTS questions on the subject of permutations and combinations of probabilities are still low in understanding the problem, good enough in re-planning, good enough in solving problems, and quite low in re-examining.